Ayat-Ayat Quran tentang Manajemen Kesiswaan (Studi Kasus Penerimaan Peserta Didik Baru di SMPN 5 Dusun Selatan) - Oktoberia, Selva Susila; Norhanah, Norhanah; Fajrin, Muhammad (Ummul Qura Jurnal Institut Pesantren Sunan Drajat (INSUD) Lamongan, 2025)
This research aims to analyze the application of student management from the perspective of the Koran with a case study of new student admissions (PPDB) at SMPN 5 Dusun Selatan. The rapid development of technology and globalization has caused concerns about moral degradation among children, so education is needed that is based on the values ​​of the Koran. This research uses descriptive qualitative methods by collecting data through documentation, observation and interviews. The research results show that the acceptance of new students at SMPN 5 Dusun Selatan follows the principles of the Koran, especially in terms of planning, acceptance, orientation, placement, coaching and evaluation of new students.